Perancangan Sistem E-Voting pada Pemilihan Ketua dan Wakil Ketua OSIS di SMK Kesuma Bangsa I Depok Berbasis Web - Mutiara Ainun Shafa; Ari Syaripudin (Journal of Artificial Intelligence and Innovative Applications (JOAIIA), 2021)
This final project research is in the form of designing an e-voting system for the selection of student councils at SMK Kesuma Bangsa 1 Depok, which at the time of this research was still conducting manual elections while the pandemic limited teaching and learning activities including the selection of student councils. E-voting is a method of voting using electronic media. This system is web-based and designed using the SDLC or Software Development Life Cycle method which consists of several stages, namely, analysis, design, coding, testing, and maintenance. The programming language used is PHP and MySQL as RDBMS. With this system, the Student Council of SMK Kesuma Bangsa 1 Depok can continue to carry out the election of chairman and deputy chairman without violating health protocols and free from fraud. It is hoped that this system can help OSIS carry out its annual activities, namely the election of the chairman and vice chairman of the OSIS.